Lithium–Sulfur Batteries: 3D CNTs/Graphene‐S‐Al3Ni2 Cathodes for High‐Sulfur‐Loading and Long‐Life Lithium–Sulfur Batteries (Adv. Sci. 7/2018). Issue 7 (18th July 2018) - Guo, Zeqing; Nie, Huagui; Yang, Zhi; Hua, Wuxing; Ruan, Chunping; Chan, Dan; Ge, Mengzhan; Chen, Xi'an; Huang, Shaoming
Abstract : In article1800026, Huagui Nie, Zhi Yang, Shaoming Huang, and co‐workers report a carbon nanotube (CNT)/graphene‐S‐Al3 Ni2 cathode with a 3D network structure. Benefiting from the 3D network to provide efficient channels for rapid electron and ion transfer, and from the incorporation of Al3 Ni2 to promote conversion reactions of lithium polysulfide species, the cathode shows excellent cycling stability and high capacity retention.